The Costs of Exhibiting Organizational Citizenship Behavior. Issue 6 (6th October 2016) - Deery, Stephen; Rayton, Bruce; Walsh, Janet; Kinnie, Nicholas
Abstract: Organizational citizenship behavior (OCB) has been associated with positive organizational outcomes and with higher managerial ratings of employee performance. However, concerns have been raised about the possible personal costs of performing such activities. This paper examines the relationship between OCB and emotional exhaustion and work‐family conflict and explores the moderating role of job performance in shaping those relationships. In a time‐lagged field study of customer‐contact center employees the research found that one particular dimension of OCB—conscientiousness—was associated with higher emotional exhaustion and with work‐family conflict. The study also revealed that conscientious employees who performed their in‐role job responsibilities at a high level experienced greater emotional exhaustion and work‐family conflict than conscientious employees who performed their in‐role job responsibilities at a low level. Our findings suggest that organizational pressures to increase the level at which both discretionary and formal role obligations are performed can carry negative consequences for employees. © 2016 Wiley Periodicals, Inc.